EMPLOYEE PERCEPTION OF STRATEGIC CHANGE MANAGEMENT AT TOURISM FUND, KENYA - Maalim, Rumana Mohamed; Muindi, Ms. Florence (Journal of Public Policy and Administration, 2016)
Purpose: The objective of the study was to establish the employee's perception of strategic change management at Tourism Fund Methodology: A survey research design was used in this study because the study was interested in establishing the opinions of more than one employee. The study populations are all employees of the Tourism Fund (CTDLT) Kenya. The respondents were 100 employees. This formed the population. The collected data was analyzed using quantitative procedures. Quantitative data was analyzed using descriptive statistics. The descriptive statistics involved frequencies, standard deviation and means. Results: The study findings indicated that the organization had established a sense of urgency in the need of change, it also created the guiding coalition for all employees to follow during the process and the company developed a vision and strategy that can be achieved. Results further revealed that the organization ensured there was good communication strategies for communicating the change vision to all employees, and ensured that all employees were empowered with broad-based action which helped the employees feel empowered to adopt the new changes. The study findings also indicated that the company ensured that it generated short-term wins, consolidated gains and producing more change and anchored new approaches in the culture Unique contribution to theory, practice and policy: Following the study findings it is possible to conclude that the employees were made part of the strategic change management thus the company had a smooth transition this was reached to as majority of the statements attracted a mean score of 3 and above which means the agreed. It was also possible to conclude that the strategies that the company selected and put aside to impose change management were favored by the employees. These strategies included creating the guiding coalition, developing a vision and strategy, communicating the change vision to employees, empowering broad-based action, generating short-term wins, consolidating gains and producing more change and anchoring new approaches in the culture. The study recommends that Managers at Tourism Fund can use the results to craft strategies on which areas to improve and which areas to excel at. For instance, the managers may highlight the toughest challenges so that they may find ways to improve on the drivers of the weaknesses and also identify the drivers of Strengths with an intention to excel in these areas. It is also suggested that since the employee perceptions were that formation of strategic change management have brought about competitive advantages, it may be important to consider investing in the area of change management with a hope of building and enjoying further competitive advantages. This investment would take the form of more human and financial resources allocated to strategic change management.